Effects of the application techniques of self-adhesive resin cements on the interfacial integrity and bond strength of fiber posts to dentin - Ana Paula Ribeiro do Vale Pedreira; Paulo Henrique Perlatti D'Alpino; Patrícia Nóbrega Rodrigues Pereira; Sasha Braun Chaves; Linda Wang; Leandro Hilgert; Fernanda Cristina Pimentel Garcia
ABSTRACT Objective: To evaluate the influence of an application technique of a glass-fiber post using self-adhesive resin cements on the push-out bond strength and the presence of bubbles in the root thirds. The cements were either applied according to the manufacturer's instruction or using a commercial delivering system (Centrix), at which the cement pastes were collected and applied after manipulation. Material and Methods: Self-adhesive resin cements (RelyX U200/3M ESPE-U200; Maxcem Elite/Kerr-MAX; Clearfil SA Cement/Kuraray-CSA) and a conventional cement (RelyX ARC/3M ESPE-ARC) were used to cement a post and applied either based on the manufacturer's instructions or using a Centrix syringe to deliver the cements directly onto the post of choice, or directly into canal. The roots were scanned with a micro-computed tomography (μCT) and then sectioned into nine 1-mm thick slices for a push-out bond strength test. The μCT images showed the percentage of bubbles in the root thirds (cervical, medium, and apical). Data were analyzed with three-way ANOVA/Tukey (α=0.05). Results: Triple interaction was not significant (p>0.05). The interaction "material" vs "root third" was not significant. A significant interaction was observed between "material" vs "application technique" (p<0.05). For ARC, U200, and MAX, significantly lower percentages of bubbles were observed when the Centrix syringe delivered the cements. Equivalent percentages of voids were observed for CSA, irrespective of the application technique (p>0.05). Significantly higher bond strength was observed when the self-adhesive resin cements were applied using the Centrix delivery system, in comparison with the manufacturer's instructions (p<0.05). Bond strength varied with the root third: cervical>medium>apical (p<0.05). No correlations were found between the bond strength and voids. Conclusions: Bond strength and voids are negatively influenced by the conventional application technique for luting fiber posts. The delivery system (Centrix) seems to produce better results when cementing fiber posts.